Effective blended learning practices evidence-based perspectives in ICT-facilitated education - Stacey, Elizabeth, 1949-; Gerbic, Philippa, 1954- (Information Science Reference, 2009)
"This book provides insight into the practice of blended learning in higher education"--Provided by publisher.